Financial planning and financial well-being of B40 households with disabled children: Questionnaire validation - Ong, Hock Siong; Nawi, Hafizah Mat; Mohaiyadin, Norlaila Mazura Hj.; Jusoh, Mohd Abdullah; Ahmad, Mohd Yusof (Edelweiss Applied Science and Technology, 2025)
This study assesses the reliability and validity of a newly developed questionnaire measuring financial planning and financial well-being among B40 households with disabled children. The instrument was adapted from established 5-point Likert scale measures found in existing literature. A total of 50 responses were collected and analyzed using SPSS Version 29.0. The scale purification process involved testing for reliability and conducting exploratory factor analysis (EFA). Results indicate high internal consistency, with Cronbach’s alpha values exceeding 0.7 across all constructs. Of the original 108 items, 97 were retained, representing 11 constructs aligned with the theoretical model. Factor loadings were strong and consistent for each construct, and the Kaiser-Meyer-Olkin (KMO) values surpassed 0.7, supporting the adequacy of the sampling. This study contributes to theory building and validation by verifying the conceptualization and operationalization of key constructs, offering a replicable framework for future research on financial planning and well-being among vulnerable households.